Air Quality Assessment in an Oil and Gas Field at Atrush Area With Particulare Reference to Sulfur Dioxide and Nitrogen Dioixde - Omar Musheer Assaf; Siraj Mohammed Abdulla (Science Journal of University of Zakho, 2023)
The effectiveness and usability of a diffusion tube for air quality sampling were assessed at 14 sites throughout an oil and gas production area in Atrush sub-district for measurement of Sulfur dioxide (SO2) and nitrogen dioxide (NO2) in ambient air by Palmes diffusion tubes in air during autumn and winter season of 2021-2022.  Using triethanolamine as a trapping agent, the passive sampler collects SO2 and NO2, which are then proven to be sulphate and nitrite using ion chromatography and visible spectrometry. Ion chromatography was used to determine the respective dissolved ionic forms of SO2. Additionally, Ultraviolet-Visible (UV-Vis) spectrophotometry used to analyse NO2 as nitrite. Sulfur dioxide (SO2) concentration was high in locations close to flare with high elevation, as well as in winter season were higher than that of autumn season, the highest average of CPF (Central Processing Facility) is (26.39 ppb), however the highest concentration recorded is below Iraqi standard limit 140 ppb for 24 hr and lowest average at ECP3(Entry Check Point 3) (4.37 ppb) respectively. Nitrogen dioxide (NO2) concentrations were high in locations where heavy equipment’s operated and in diesel consumption areas, highest average of NO2 concentration of E pad (East Pad) is (8.94 ppb), and lowest average was in ECP3 (3.09 ppb).